PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V DI SD NEGERI 173604 PANGURURAN - Ibelisa R Pasaribu; Antonius Remigius Abi; Patri Janson Silaban; Eka Margareta Sinaga; Frikson Jony Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the Project Based Learning model on the IPAS learning outcomes of fifth grade students at SD Negeri 173604 Pangururan in the 2024/2025 academic year. The method used was quantitative with the population being all fifth-grade students at SD Negeri 173604 Pangururan, while the research sample consisted of 22 students determined through boring sampling (total sampling). Data on the Project Based Learning model was obtained through a questionnaire distributed to students, while learning outcome data was obtained from students' pretest and posttest scores in the 2024/2025 academic year. The results showed that student learning outcomes with the application of Project Based Learning were in the very good category with an average posttest score of 80.18. The correlation test showed a value of 0.811, which means that rcount 0.811 ≥ rtabel 0.444, so Ha was accepted. Thus, there is a very strong influence between the application of Project Based Learning and the IPAS learning outcomes of fifth-grade students at SD Negeri 173604 Pangururan This is also reinforced by the t-test results, which show that tcount ≥ ttable, namely 6.192 ≥ 1.717 so Ha is accepted. Based on these results, it can be concluded that the use of the Project Based Learning model has a positive and significant effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 173604 Pangururan in the 2024/2025 academic year.